A hydatidiform mole in a postmenopausal woman - Dhanapal, Mohana; Padmapriya, .; Pandian, Anbarasi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Gestational trophoblastic disease occurs in less than 1 per 1200 pregnancies. The spectrum of this disease ranges from benign hydatidiform mole to trophoblastic malignancy (placental-site trophoblastic tumor and choriocarcinoma). Benign gestational trophoblastic disease generally occurs in women of reproductive age and is extremely rare in postmenopausal women. We report a case of a 54-year-old postmenopausal woman who underwent an emergency total abdominal hysterectomy due to uncontrollable vaginal bleeding associated with an increased serum β-human chorionic gonadotropin level. The resected uterus contained an endometrial, cystic, grapelike tumor. Microscopic examination demonstrated hydropic degenerated villi with a circumferential trophoblastic cell proliferation and moderate atypia, consistent with a complete hydatidiform mole. Only isolated cases of hydatiform mole in elderly women have been reported in literature. But there still remains a risk of developing gestational trophoblastic disease in the elderly and it should always be included in the differential diagnosis of postmenopausal bleed.